STRATEGIES OF PHYSICAL EDUCATION TEACHERS IN INTEGRATING TRADITIONAL GAMES INTO PHYSICAL EDUCATION AND HEALTH LEARNING IN ELEMENTARY SCHOOLS - Sri Wahyuni Br Silitonga; Sukendro; Ugi Nugraha; Ilham; Reza Hadinata; Hendri Munar; Nabil Afiqra Febriza (El Midad, 2026)
The integration of traditional games into Physical Education, Sports, and Health (PJOK) learning can strengthen student engagement, develop motor skills, and instill cultural values. However, the success of integration is largely determined by the teacher’s strategy in planning, implementing, and contextually evaluating learning. This study aims to describe PJOK teachers’ strategies in integrating traditional games into PJOK learning in elementary schools. The study uses a qualitative case study design. Data were collected through semi-structured interviews with PJOK teachers, participatory observation of the implementation of learning, and a study of teaching materials. Data analysis followed an interactive analysis model combined with thematic analysis to produce the main strategy themes. The results of the study show that teachers’ strategies are grouped into six themes: (1) mapping movement objectives and time allocation; (2) selecting games based on competence and environmental context; (3) modifying rules, tools, and space for safety and inclusiveness; (4) classroom management based on small groups, stations, and control signals; (5) internalization of cultural values through reflection and value language; and (6) process-outcome evaluation using rubrics, checklists, journals, and video-based reflection. The findings confirm that traditional games are effective vehicles for holistic learning when structured activities are aligned with learning outcomes and student needs.